METHODS FOR RESEARCHING THE CULTURAL AND NATIONAL VARIATIONS OF SOMATIC PHRASES (Konferensiyalar | Conferences, 2024)
Somatism is one of the oldest layers in the vocabulary of different languages, reflecting the cultural and national characteristics of peoples, their customs and traditions, conveying many years of experience and culture, their spirit, demonstrating the influence of foreign language factors on the language. An important expression of concepts and, therefore, they belong to a stable parts of many languages [4, 20].